2023
DOI: 10.1088/1755-1315/1259/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Response of Yield Traits and its Components to Sesame Genotypes for Different Plant Distributions

Nisreen Jamal Khattab,
Hussein Ali Hindi Al-Bayati

Abstract: A field experiment was carried out at the research station of the Department of Field Crops at the College of Agriculture at the University of Tikrit in Salah al-Din Govemorate under gypsum soil conditions during the summer agricultural season (2022 AD), to evaluate the performance of six sesame genotypes, namely (Al-Mahalli, Wada’, Had, Sumer, Rafidain and Baytim) and three distributions. Plants, which are (60 x 10, 40 x 15, and 30 x 20) cm2, and Interaction between two factors of the study in traits, yield, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This result agreed with the previous results of several studies that showed the difference in sesame varieties in the number of capsules in the plant. They attributed the reason for the genetic variation and the suitability of the variety to the environmental conditions and how can invest the available growth requirements towards the yield components [18][19][20]. As for the interaction between the study factors, was also significant.…”
Section: Number Of Capsules Per Plantmentioning
confidence: 99%
“…This result agreed with the previous results of several studies that showed the difference in sesame varieties in the number of capsules in the plant. They attributed the reason for the genetic variation and the suitability of the variety to the environmental conditions and how can invest the available growth requirements towards the yield components [18][19][20]. As for the interaction between the study factors, was also significant.…”
Section: Number Of Capsules Per Plantmentioning
confidence: 99%